Electrocatalytic Water Oxidation: An Overview With an Example of Translation From Lab to Market - Sen, Rakesh; Das, Supriya; Nath, Aritra; Maharana, Priyanka; Kar, Pradipta; Verpoort, Francis; Liang, Pei; Roy, Soumyajit (Frontiers in Chemistry, 2022)
Water oxidation has become very popular due to its prime role in water splitting and metal-air batteries. Thus, the development of efficient, abundant and economical catalysts as well as electrode design is very demanding today. In this review, we have discussed the favorable thermodynamics for electrochemical reactions, the electrocatalyst and electrode design strategies for most efficient results and recent advancement in OER catalyst design. Finally, we have discussed use of OER in Oxygen Maker (OM) design with the example of OM REDOX by Solaire Initiative Private Ltd. The review clearly summarizes the future directions and applications for sustainable energy utilization with the help of water splitting and way forward to develop better cell designs with electrodes and catalysts for practical applications. We hope this review will offer basic understanding of OER process and WOR in general along with the standard parameters to evaluate the performance and encourage more WOR based deep innovations to make their way from the lab to the market following the example of OM REDOX.